1999
DOI: 10.1097/00006534-199903000-00028
|View full text |Cite
|
Sign up to set email alerts
|

A New Transfacial Approach for Lesions of the Clivus and Parapharyngeal Space: The Partial Segmented Le Fort I Osteotomy

Abstract: Tumors of the clival and parapharyngeal areas are a challenge because of their location. They used to be considered inaccessible because the aggressive approaches employed caused elevated levels of morbidity. This fact led to more conservative approaches that attempted to preserve the exposure of the lesion. These approaches were a combination of cranial and facial procedures, thus utilizing a combined effort between neurosurgeons and maxillofacial surgeons. We described our experience with a partial segmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…These are the approaches of choice for median-line tumors that protrude into the posterior pharynx and extend from the clivus to C3. 4 In our patient, the tumor was large, occurred near the median line of the retropharyngeal space, extending from the clivus to the level of the C2-C3 disc, and did not invade the vertebral arteries or spinal canal. The route of a biopsy performed at another hospital was transoral.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These are the approaches of choice for median-line tumors that protrude into the posterior pharynx and extend from the clivus to C3. 4 In our patient, the tumor was large, occurred near the median line of the retropharyngeal space, extending from the clivus to the level of the C2-C3 disc, and did not invade the vertebral arteries or spinal canal. The route of a biopsy performed at another hospital was transoral.…”
Section: Discussionmentioning
confidence: 54%
“…this approach or a modified form of it. 4,5 The benefits of frontal approaches are that the median line is less vascular, the surgical distance is minor relative to that involved in lateral approaches, the masticatory muscles and neurovascular structures can be avoided, and facial incisions are minimal because of the degloving property of the facial tissues. The disadvantage is that it is difficult to reach the lateral extensions of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chordoma have reported 5‐ and 10‐year survival rates of 51% and 35%, respectively, after surgery followed by radiotherapy 25,26,28 . Trotter's surgical technique has been used in combination with Le Fort I osteotomy and mid facial degloving in the management of clivus and upper cervical spine chordomas 18,20,21 . The Trotter's median labiomandibular glossotomy approach alone was used in our case and we obtained good exposure from C1‐C3/4 cervical vertebra.…”
Section: Discussionmentioning
confidence: 70%
“…Various surgical approaches have been described in the literature to access the clivus and upper cervical spine, which include transmaxillary, transmandibular, mandibular swing, transpalatal, transoral, transcervical, high anterior cervical and lateral approach. Sometimes, combinations of approaches are used to gain adequate access for chordomas of the upper cervical spine 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…Good surgical technique is paramount, avoiding excessive pulling of the maxillary vascular pedicle or excess palatine mucosa detachment; these measures favor adequate postoperative vascularization even in procedures lasting over 10 hours, such as these. 8,9 Intraoperative hemorrhage may result from excessive stretching of the descending palatine artery or injury to the pterygoid plexus during disjunction of the pterygomaxillary process, especially if the osteotome is placed incorrectly or if excessive force is applied during osteotomy. Some authors have suggested that the descending palatine artery should be ligated to minimize the risk of intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%